Penapisan dan Identifikasi Bakteri Agens Biokontrol Penyakit Layu Fusarium Hasil Isolasi dari Rizosfer Pisang - Dwi Agustiyani; Achirul Nditasari; Nur Laili; Sarjiya Antonius (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2014)
Banana wilt disease caused by Fusarium oxysporum f.sp.cubense is considered as one of the most destructive diseases on banana plants in the tropical region. Biological control agents (BCA’s) have become a promising solution to overcome this disease. The objective of this study was to find potential BCA’s for wilt disease of banana plants. Bacteria and actinomycetes were isolated from banana’s rhizosphere in Lampung and Cianjur. As much as 64 actinomycetes and 142 bacteria isolates were obtained. Antagonistic test against F. oxysporum f. sp. cubense of those isolates showed that 21 bacteria and 10 actinomycete isolates have abilities to inhibit F. oxysporum f. sp. cubense. Actinomycetes showed relatively higher inhibition against F. oxysporum f. sp. cubense compared to bacteria. Isolates which have positive antagonistic activities against F. oxysporum f. sp. cubense were then tested for their protease, chitinase, and selulase activities qualitatively on specific medium. All actinomycetes which were tested had chitinase enzyme activities, while only 5 bacterial isolates had chitinase activities. On the other hand, 13 bacterial isolates showed protease activities and only 1 actinomycete showed protease activity. Two bacterial isolates (L.II.4.ND and L.A.I-5.DW) and 3 actinomycetes (L.A.I.DW, L.3.1.DW and Ci.I.A5.DW) which showed high inhibition against F. oxysporum f. sp. cubense and lyses enzymes activities were identified based on 16S rRNA genes. Analysis based on GenBank data, those isolates have 99% homology to Klebsiella pneumonia (L.II.4.ND), Burkholderia sp. (L.A.I-5.DW), Streptomyces sp. (L.A.I.DW), Streptomyces sp. (L.3.1.DW) and Streptomyces sp. (Ci.I.A5.DW).